Inflmatory response to Tocilizumab in pacients with COVID-19 in Lima. : Retrospective multicenter study - Balarezo-Aguilar, Sebastián Javier (2020)
Background: In the present study, Tocilizumab(TCZ) was used in patients with COVID-19, who had clinical deterioration and meet the inclusion criteria, previously established by an expert panel (IL-6 >40,, Ferritine >500, PCR >10, Linfopenia <500). Methods: In a single-arm, multicenter (3 private hospital from Lima, Peru), descriptive, retrospective study adult hospitalized COVID-19 patients were included. The clinical and laboratory parameters were collected prior to the administration of TCZ and 24-48 hours after finnishing it. Data was analysed as the mean ± standard deviation for continuous variables and as an absolute value with percentages for categorical variables. The t-student test was used to compare the variables using SPSS, version 23.0. Results: A total of 20 patients (14 men, age 61.9 ± 12.7) with laboratory confirmation (PCR or serological test) for Covid-19 were included. The mortality rate was 15% (3/20 patients). No adverse events related to the use of TCZ were reported. A significant decrease in C reactive protein levels and an increase in platelets levels was observed. Conclusions: TCZ does not increase mortality in comparison to other studies and it improves the inflammatory state of patients. It could be associated with a prothrombotic events due to D-Dimer and platelets increase, but more studies are needed